2009
DOI: 10.1007/s12010-008-8491-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Oleaginous Yeast Strains Tolerant to Lignocellulose Degradation Compounds

Abstract: High cost of triacylglycerol lipid feedstock is the major barrier for commercial production of biodiesel. The fermentation of oleaginous yeasts for lipid production using lignocellulose biomass provides a practical option with high economic competitiveness. In this paper, the typical oleaginous yeast strains were screened under the pressure of lignocellulose degradation compounds for selection of the optimal strains tolerant to lignocellulose. The inhibitory effect of lignocellulose degradation products on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(117 citation statements)
references
References 15 publications
5
108
0
4
Order By: Relevance
“…O gênero Yarrowia é conhecido na literatura por sua capacidade de acumular lipídios (Chen et al, 2009;Signori et al, 2016). Este estudo comprovou que todos os isolados de Yarrowia coletados nos laticínios da bacia do Agreste-PE apresentaram potencial de crescimento e de acúmulo de lipídios, utilizando o glicerol bruto como fonte de carbono.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O gênero Yarrowia é conhecido na literatura por sua capacidade de acumular lipídios (Chen et al, 2009;Signori et al, 2016). Este estudo comprovou que todos os isolados de Yarrowia coletados nos laticínios da bacia do Agreste-PE apresentaram potencial de crescimento e de acúmulo de lipídios, utilizando o glicerol bruto como fonte de carbono.…”
Section: Discussionunclassified
“…Muitas vantagens estão envolvidas no uso de leveduras oleaginosas para a produção de lipídios, como a alta taxa de crescimento em biorreatores, a capacidade de assimilar diversas fontes de carbono e não serem afetadas por limitações de espaço, clima ou variações de luz (Ami et al, 2014). Entre as leveduras mais citadas na literatura, como oleaginosas, figuram as do gênero Rhodotorula e da espécie Yarrowia lipolytica (Chen et al, 2009;Signori et al, 2016).…”
Section: Introductionunclassified
“…Oleaginous bacterial accumulation of lipids for biofuel production from industrial waste is being studied extensively [41][42][43][44][45][46][47]. Transcriptomic and proteomic studies have also identified TAG biosynthetic genes and proteins [48][49][50][51][52][53].…”
Section: Oleaginous Lipid Accumulation In Rhodococcus Opacusmentioning
confidence: 99%
“…Many studies have explored the use of common oleaginous yeast species in single-cell oil (SCO) production (Breuer and Harms, 2006;Chen et al, 2009;Magdouli et al, 2014). Table 1 shows the typical oleaginous yeast species that were used for bioconversion of cellulosic sugars to SCO.…”
Section: Introductionmentioning
confidence: 99%
“…Using renewable materials as substrates can enhance the economy of the bioconversion process for Y. lipolytica (Chen et al, 2009;Liang and Jiang, 2013). Molasses, N -acetylglucosamine, sewage sludge, palm oil mill, olive oil mill wastewater, whey, municipal wastewater, industrial fats, and saturated spent fat are examples of such materials (Barth and Gaillardin, 1997;Papanikolaou et al, 2003;Fickers et al, 2005;Chen et al, 2009;Thevenieau and Nicaud, 2013).…”
Section: Introductionmentioning
confidence: 99%